Tumour suppression by targeted intravenous non-viral CRISPRa using dendritic polymers. Issue 33 (5th July 2019) - Kretzmann, Jessica A.; Evans, Cameron W.; Moses, Colette; Sorolla, Anabel; Kretzmann, Amy L.; Wang, Edina; Ho, Diwei; Hackett, Mark J.; Dessauvagie, Benjamin F.; Smith, Nicole M.; Redfern, Andrew D.; Waryah, Charlene; et al.
Abstract : This article demonstrates a fully synthetic strategy enabling CRISPR-mediated activation of tumour suppressor genes in vivo to reduce tumour burden. Abstract : Aberrant gene expression is a hallmark of cancer. Although transcription is traditionally considered 'undruggable', the development of CRISPR-associated protein 9 (Cas9) systems offers enormous potential to rectify cancer-associated transcriptional abnormalities in malignant cells. However delivery of this technology presents a critical challenge to overcome in order to realize clinical translation for cancer therapy. In this article we demonstrate for the first time, a fully synthetic strategy to enable CRISPR-mediated activation (CRISPRa) of tumour suppressor genes in vivo using a targeted intravenous approach. We show this via highly efficient transcriptional activation of two model tumour suppressor genes, Mammary Serine Protease Inhibitor (MASPIN, SERPINB5 ) and cysteine-rich 61/connective tissue growth factor/nephroblastoma-overexpressed 6 ( CCN6, WISP3 ), in a mouse model of breast cancer. In particular, we demonstrate that targeted intravenous delivery of can be achieved using a novel nanoscale dendritic macromolecular delivery agent, with negligible toxicity and long lasting therapeutic effects, outlining a targeted effective formulation with potential to treat aggressive malignancies.